Cuisine and symbolic capital : food in film and literature - Mahar, Cheleen (Newcastle upon Tyne : Cambridge Scholars, 2010)
This collection of interdisciplinary essays examines food as it mediates social relationships and self-presentation in a variety of international films and literature. Authors explore the ways that making, eating and thinking about food reveals culture.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Food in motion pictures; Food in literature; Electronic books